2015
DOI: 10.1167/iovs.15-17174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity Within the Clinical Diagnosis of Pericentral Retinal Degeneration

Abstract: METHODS. Patients were screened for an annular ring scotoma ranging from 38 to 408 (n ¼ 28, ages 24-71) with kinetic perimetry. All patients had pigmentary retinopathy in the region of the dysfunction. Further studies included cross-sectional and en face imaging, static chromatic perimetry, and electroretinography. Molecular screening was performed.RESULTS. Genotypes of 14 of 28 PRD patients were identified: There were mutations in eight different genes previously associated with autosomal dominant or autosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
5
19
1
Order By: Relevance
“…Similarly, Berson et al [29] reported that 54% of RP patients aged ≥40 years had a visual acuity of 20/40 or better (85% in our cases aged ≥40 years). Furthermore, the GVF area estimated in pericentral RP was wider compared to typical RP, in agreement with the above-cited studies [3][4][5]. In particular, the GVF area measured with V4e target appeared markedly more preserved in pericentral RP patients compared to a large cohort (n = 601) of typical RP patients recruited in a clinical trial investigating the effects of vitamin A treatment in RP [30].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, Berson et al [29] reported that 54% of RP patients aged ≥40 years had a visual acuity of 20/40 or better (85% in our cases aged ≥40 years). Furthermore, the GVF area estimated in pericentral RP was wider compared to typical RP, in agreement with the above-cited studies [3][4][5]. In particular, the GVF area measured with V4e target appeared markedly more preserved in pericentral RP patients compared to a large cohort (n = 601) of typical RP patients recruited in a clinical trial investigating the effects of vitamin A treatment in RP [30].…”
Section: Discussionsupporting
confidence: 88%
“…Pericentral RP was found to be associated with a better visual acuity compared to typical RP. Indeed, almost all patients (85.2%) showed a preserved BCVA of 20/40 or better in at least one eye, in line with the previous studies on pericentral RP that reported a percentage of 71% and 94% [3][4][5]. In particular, in a large US cohort of typical RP (about 900 cases), only 55% of subjects had a visual acuity of 20/40 or better [27].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…At later disease stages, there is normal sensitivity across the visual field and an annular ring of S-cone dysfunction that can coincide with pigmentary changes in a region extending from approximately 108 to 408, a region that has been described as pericentral or near peripheral. 30 These data confirm the impression from the sample of six patients ( Figs. 2A-F).…”
Section: What Is the Regional Variation Of S-cone Sensitivity In Patisupporting
confidence: 85%